Action Contribution to Competence Judgments: The Use of the Journey Schema - Horchak, Oleksandr V.; Giger, Jean-Christophe; Garrido, Margarida V. (Frontiers in Psychology, 2016)
The current research considered the question of how performing an action, or merely preparing the body for action, can have an impact on social judgments related to person perception. Participants were asked to ascribe competence and warmth characteristics to a target person by reading a metaphoric text while their body was manipulated to be prepared for the processing of action-congruent information. In Experiment 1, participants whose forward body action matched the metaphoric action described in the text ascribed more competence characteristics to a politician than did control participants. In Experiment 2, participants whose body was merely prepared for forward movement also ascribed more competence characteristics to a politician than did control participants. In addition, the data from Experiment 2 ruled out an alternative non-embodied explanation (i.e., that effect is due to basic associative processes) grounded in the existing literatures on attitudes by demonstrating that body manipulation had no effect on competence when a non-metaphoric text was used. Finally, no evidence was found that body manipulation affects warmth judgments. These studies converge in demonstrating that forward body movements enhance the favorability of competence judgments when these match the metaphoric forward movements described by text.